Employment Protection, Workforce Mix and Firm Performance - Chiara Ardito; Fabio Berton; Lia Pacelli; Filippo Passerini (Institute of Labor Economics (IZA), 2021)
We measure the impact of employment protection reduction in an uncertain framework on firms' hires and performance, exploiting the Italian 2015 Jobs Act. Results indicate that firms (1) stabilize workforce mainly through contract transformations of low-tenure and low-human-capital incumbent workers performing high-physical and low-intellectual tasks; (2) apply a cost-saving strategy that increases profits and decreases value added per-head. Effects are stronger among non-exporting and non-innovative firms. Our evidence casts doubts on the effectiveness of employment protection reductions in enhancing productivity in the long run.
Keywords: J08; J21; J24; 330; employment protection; human capital; productivity; tenure; tasks